MRI Findings In Patients With Headache And Vertigo - Waheed, Tahreem; Zulfiqar, Taiba; Ali, Abid (Medical Science Journal for Advance Research, 2022)
BACKGROUND:A headache is a condition of pain in the head. In Medical nomenclature, it is known as cephalgia.Primary and secondary headaches are the two forms of headaches. The first type of headache is primary headache, which includes migraine, cluster headaches, and tension headaches. They are non-aggressive in nature. Primary headaches are usually chronic in character and are caused by no underlying functional illness. The second type of headache is secondary headache, which is always brought on by major organic disorders. It can range from benign cranial conditions like sinusitis or mastoiditis to life-threatening intracranial pathologies like subarachnoid haemorrhage or brain tumours. Vertigo is a perception of motion or spinning that is often represented as dizziness. Vertigo is not the same as being featherbrained. People with vertigo tone as though they are actually handicraft or moving, or that the world is spinning around them. Vertigo is frequently caused by issues with certain regions of the brain. Vertigo can be caused by a variety of factors, including benign paroxysmal positional vertigo (BPPV), which occurs when certain head motions cause vertigo. Migraines are a type of severe headache. Mostly the patients with vertigo and headache normally do not require a brain MRI. For Secondary reason of headache,some patients need an brain MRI. MRI is best Diagnostic modality for the diagnosis and management of secondary headache and vertigo. CONCLUSION: Magnetic resonance imaging (MRI) is a finest diagnostic modality that creates detailed images of the organs and tissues in your body using a magnetic field and computer-generated radio waves. It is considered as the best diagnostic method for the diagnosis and therapy of secondary headache and vertigo. A modest percentage of medical institution fundamental positive findings in neuroimaging are seen in MRI of patients with headache. In these patients, the cost-effectiveness of MRI as a screening tool is of limited benefit.